Efektivitas Pelaksanaan Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan Berkaitan dengan Modifikasi Kendaraan Bermotor di Kota Bukittinggi Ditinjau dari Perspektif Siyasah Tanfidziyah - Sasa Sakinah; Hamdani Hamdani (AHKAM, 2026)
Studies on employee retention have been widely conducted, yet research that specifically discusses the effects of compensation, job satisfaction, and career development on employee retention at PT Sarana Sumatera Barat Ventura remains limited. This study aims to analyze the effects of compensation, job satisfaction, and career development on employee retention at PT Sarana Sumatera Barat Ventura. This study used a quantitative approach with a survey design. The research respondents consisted of 34 employees determined using total sampling. Data were collected through questionnaires and then analyzed through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing with the assistance of SPSS. The results show that compensation has no significant effect on employee retention. Job satisfaction has a positive and significant effect on employee retention, whereas career development has no significant effect on employee retention. This finding broadens understanding of the factors that influence employee retention in the context of a regional financial company. The conclusion of this study emphasizes that job satisfaction is an important factor in increasing employee retention at PT Sarana Sumatera Barat Ventura. The practical implications of this study indicate the need for the company to prioritize improving job satisfaction as the main strategy for retaining employees and supporting human resource stability.